Human Development in Crisis: Insights from the Literature, Emerging Accounts from the Field, and the Correlates of Growth Accelerations and Decelerations - Conceicao, Pedro (Archīum Ateneo, 2010)
Is a dramatic slowdown in global economic growth going to erase much of the progress in the last decade in terms of human development in the developing world‘ How might the crisis affect progress towards achieving the Millennium Development Goals‘ To address these questions, this paper contributes in three ways. First, it briefly reviews the empirical literature and outlines the possible transmission of the crisis from the broader global economy to the national economy, and eventually to households, children and women. Second, it summarizes some of the emerging accounts from the field based on reports and interviews of poor people, suggesting that households - and in particular children and women - face severe strain as the crisis has begun to unfold. A third contribution is an empirical analysis of the historical relationship between episodes of growth accelerations and decelerations with country level aggregate indicators of human development (e.g. life expectancy, infant and under-5 mortality and school enrollment), using data covering the period between 1980 and 2006. This paper argues that if the current economic crisis deteriorates into a severe growth deceleration episode, and if its adverse effects are not contra veiled by an adequate policy response, the accumulated evidence suggests that the crisis could begin to erode human development gains and that the achievement of the MDGs by 2015 is likely to be undermined.